1996
DOI: 10.1111/j.1476-5381.1996.tb15406.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional haemodynamic effects of antagonists of angiotensin II, endothelin and adrenoceptors in conscious, vasopressin‐deficient, genetically hypertensive rats

Abstract: 1. Male, vasopressin-deficient, normotensive (DI/N) and hypertensive (DI/H) rats were chronically instrumented (all surgery under sodium methohexitone anaesthesia) to allow assessment of resting haemodynamic status and responses to antagonism of AT1-receptors (Experiment 1), ET(A-) and ET(B-) receptors (Experiment 2) or adrenoceptors (Experiment 3). 2. Before any treatment, mean arterial blood pressure (MAP) was higher, and hindquarters vascular conductance was consistently lower in all groups of DI/H rats tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Infusions of angiotensin I or of angiotensin II into fetal sheep produce substantial increases in fetal blood pressure (4,12,26). Similarly, infusions of angiotensin I or of angiotensin II increase arterial pressure in the adult (11,16,20,28). Blockade of type 1 angiotensin receptors results in a decrease in blood pressure (23,24,27) in the fetus and in the adult (19,28,29).…”
mentioning
confidence: 99%
“…Infusions of angiotensin I or of angiotensin II into fetal sheep produce substantial increases in fetal blood pressure (4,12,26). Similarly, infusions of angiotensin I or of angiotensin II increase arterial pressure in the adult (11,16,20,28). Blockade of type 1 angiotensin receptors results in a decrease in blood pressure (23,24,27) in the fetus and in the adult (19,28,29).…”
mentioning
confidence: 99%
“…In contrast, hypertensive transgenic ((mRen-2)27; abbreviated to TG) rats do not have elevated plasma endothelin levels, yet they show signi®cant hypotension and peripheral vasodilatation in response to SB 209670 (Gardiner et al, 1995c). This is not a non-speci®c eect of SB 209670, since the compound is without signi®cant cardiovascular action in another genetic model of hypertension (Gardiner et al, 1996d). On the basis of these ®ndings we concluded that the involvement of endothelin in the hypertension seen in TG rats might be due to an in¯uence of tissue renin-angiotensin activity (see Lee et al, 1996, for review) on local endothelin synthesis (Gardiner et al, 1995c).…”
Section: Introductionmentioning
confidence: 99%